0017 Violent deaths among first responders: using north carolina violent death reporting system data to inform injury programs. (26th April 2015) - Austin, Anna; Proescholdbell, Scott; Norwood, Tammy
Abstract : Statement of purpose: First responders, including Emergency Medical Services (EMS) personnel, law enforcement officers, and firefighters, play a critical role in ensuring the safety and wellbeing of others. However, due to the nature of their occupation, first responders are exposed to a number of violent situations and traumatic or stressful events that may increase their risk for violent death. The purpose of this study was to examine violent deaths among first responders using data collected by the North Carolina Violent Death Reporting System (NC-VDRS). Methods/Approach: Data regarding violent deaths in North Carolina were obtained from NC-VDRS for 2004 to 2011. Key word searches of occupational variables from all data sources were used to identify North Carolina residents who died as a result of violence and were current or former first responders. These deaths were compared to violent deaths among all other North Carolina residents. Results: In North Carolina between 2004 and 2011, 75 law enforcement officers, 23 firefighters, and 19 EMS personnel died as a result of violence. Of these deaths, 74% were suicides and 22% were homicides. All of the violent deaths among EMS personnel were the result of suicide, and the majority of homicide deaths were among law enforcement officers with 52% occurring while the officer was on duty. A significantly higher percentage of first responder suicide victims had an intimate partner problem and a job problem compared to all other North Carolina resident suicide victims. Conclusions: Violent death, particularly suicide, affects individuals in first responder occupations with certain circumstances being particularly prevalent. Significance and contribution to the field: Gaining a greater understanding of violent deaths among first responders provides valuable information for prevention and intervention strategies aimed at establishing a culture of safety and wellbeing in these occupations. For example, in Western North Carolina, a peer response network of first responders has used these findings to inform their efforts to promote mental wellbeing and reduce risk factors for suicide among colleagues.